Komitmen Kerja dan Kompensasi Terhadap Kepuasan Kerja Pegawai - Wasna, Wasna; Nur, Irawati; Nirwana, Nirwana; Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This research aims to determine the effect of work commitment and compensation on job satisfaction of employees of the Ministry of ATR/BPN Land Agency of Parepare City.The population used in this research were 57 employees of the Ministry of ATR/BPN of the Parepare City Land Agency using a saturated sampling technique, meaning using the entire population as the research sample. The descriptive analysis method uses a Likert scale as a measuring data was processed using SPSS software. The independent variables in this research are Work Commitment (X1), Compensation (X2). The dependent variable in this research is Job Satisfaction (Y). The results of this research show that the Work Commitment variable (X1) has a partial and significant effect on Job Satisfaction of employees of the Ministry of ATR/BPN Land Agency of Parepare City with the results obtained tcount 4.582 > ttable 1.673 with significance (0.000 < 0.05). The Compensation Variable (X2) has a partial and significant effect on Job Satisfaction of employees of the Ministry of ATR/BPN Parepare City Land Agency with the results obtained tcount 1.745 > ttable 1.673 which is significant (0.128 < 0.05). And for the work commitment variable, compensation has a simultaneous effect on the job satisfaction variable with the results obtained being Fcount (42,298) > Ftable (1.42).